2017
DOI: 10.1016/j.arcmed.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Brain-derived Neurotrophic Factor Val66Met Polymorphism and Overweight/Obesity in Pediatric Population

Abstract: This is the first study showing the significant association between the BDNF rs6265 AA (Met/Met) genotype and overweight/obesity in Mexican pediatric population.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…In terms of human study, association between Val66Met polymorphism with obesity, dyslipidaemia and diabetes are controversial. For instance, several studies have shown that Met/Met genotype have higher risk for insulin resistance, obesity and dyslipidaemia 24 , 42 , 43 . Bonaccorso et al revealed, Met-allele of BDNF Val66Met polymorphism was to be positively associated with serum levels TG and TG/HDL-C ratio 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of human study, association between Val66Met polymorphism with obesity, dyslipidaemia and diabetes are controversial. For instance, several studies have shown that Met/Met genotype have higher risk for insulin resistance, obesity and dyslipidaemia 24 , 42 , 43 . Bonaccorso et al revealed, Met-allele of BDNF Val66Met polymorphism was to be positively associated with serum levels TG and TG/HDL-C ratio 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Healthy Croatian children and adolescents carrying one or two methionine alleles tend to have higher BMI and are prone to obesity [ 3 ]. Furthermore, a Mexican study in a pediatric population showed a significant association between the Met/Met genotype and obesity [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Association studies of BDNF Val66Met polymorphism and body mass index (BMI), of healthy children and adolescents have shown contradictory results [ 3 , 11 , 12 ], while studies of association between the Val66Met polymorphism and glucose level as well as lipid status of children and adolescents are still rare [ 12 ]. The aim of this study was to investigate the association of the Val66Met (rs6265) polymorphism with BMI, fasting glucose levels and lipid profiles of healthy adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, peripheral or ventricular administration of BDNF suppresses energy intake and reduces body weight (31). In humans, BDNF haploinsufficiency or inactivating mutations of the BDNF receptor result in the hyperphagia and childhood-onset obesity (32,33). Moreover, large genome-wide association studies have strongly implicated the BDNF gene locus in the regulation of body mass index (BMI) (34).…”
Section: Introductionmentioning
confidence: 99%